Why is Automobile Insurance in Philadelphia So Damn Expensive? - Smith, Eric; Wright, Randall (American Economic Review, 1992)
We document and attempt to explain the observation that automobile insurance premiums vary dramatically across cities. We argue that high premiums can be attributed, at least in part, to large numbers of uninsured motorists in some markets, while uninsured motorists can be attributed to high premiums. We construct a simple noncooperative equilibrium model that can generate inefficient equilibria with uninsured drivers and high, yet actuarially fair, premiums. For certain parameterizations, an efficient full-insurance equilibrium and inefficient high-price equilibria with uninsured drivers exist simultaneously, helping to explain price variability across otherwise similar cities. Policy implications are discussed.